PERAN HIPPUN DALAM MEMPERKUAT IKATAN SOSIAL MASYARAKAT DI DESA GIHAM SUKAMAJU, KABUPATEN LAMPUNG BARAT - Eprida Yunara, Nadia; Andini, Sisca Dwi; Al Farabi, Muhammad Ramdhan Fathin; Sari, Mei Fatmila (Jurnal Punyimbang, 2025)
Hippun tradition is a traditional event carried out by the Lampung indigenous people, especially the West Lampung community who will carry out a wedding. The purpose of this study was to describe the role of hippun in strengthening social ties in the community of Pekon Giham Sukamaju, Sekincau District, West Lampung Regency. The results of this study found that there were a number of processes that were passed through during the hippun event and with one of the principles contained in hippun, namely sakai sambayan (mutual cooperation, helping each other) had an influence on social solidarity so that it could create a sense of empathy, sympathy and togetherness, as well as the involvement of all levels of society regardless of social class. The Hippun tradition has proven to be effective and can be used as a tool to strengthen the bonds of brotherhood and friendship between communities because they are united in one container and unite their minds so that they can achieve the same goal, there is mutual assistance between relatives, families and communities so that they create an attitude of upholding and working together in the nayuh traditional tradition so that the event can run smoothly. Penelitian ini bertujuan untuk mendeskripsikan peran hippun dalam memperkuat ikatan sosial masyarakat di Desa Giham Sukamaju, kecamatan sekincau kabupaten Lampung Barat. Hasil penelitian ini didapatkan bahwa adanya sejumlah proses-poses yang di lalui pada saat acara hippun itu berlangsung dan dengan adanya salah satu pi’il yang terkandung didalam hippun yaitu sakai sambayan (gotong royong, tolong menolong) memiliki pengaruh terhadap solidaritas sosial sehingga, dapat terciptanya rasa empati, simpati dan rasa kebersamaan, serta keterlibatan semua lapisan masyarakat tanpa memandang kelas sosial. Tradisi Hippun terbukti efektif dan mampu dijadikan alat untuk mempererat tali persaudaraan dan silaturahmi antar masyarakat karena disatukan dalam satu wadah dan menyatukan pikiran sehingga bisa mencapai tujuan yang sama, adanya saling bantu membantu antar sesama kerabat, keluarga dan masyarakat agar menjadikan sikap menjunjung tinggi serta bekerja sama dalam tradisi adat nayuh sehingga acara tersebut bisa berjalan dengan lancar.